Beyond cost: Exploring fuel choices and the socio-cultural dynamics of liquefied petroleum gas stove adoption in Peru. (August 2020) - Williams, Kendra N.; Kephart, Josiah L.; Fandiño-Del-Rio, Magdalena; Condori, Leonora; Koehler, Kirsten; Moulton, Lawrence H.; Checkley, William; Harvey, Steven A.; ,
Highlights: Behavioral training and free LPG helped participants realize the benefits of LPG. Participants accepted perceived disadvantages of LPG given the valued benefits. Reducing LPG costs and providing user support can facilitate near-exclusive LPG use. Abstract: Reducing the burden of household air pollution requires that cleaner fuels such as liquefied petroleum gas (LPG) be used nearly exclusively. However, exclusive adoption has been challenging in low- and middle-income countries. Previous studies have found that economic, social, and cultural barriers often impede adoption. We conducted in-depth qualitative interviews with 22 participants in a research trial where LPG was provided for free in Puno, Peru. We aimed to determine whether social and cultural barriers to LPG use persisted when monetary costs to the households were removed, and what factors influenced exclusive adoption of LPG in a cost-free context. Facilitators of LPG use included: support from study staff, family support, time savings, previous experience with LPG, stove design, ability to use existing pots, smoke reductions, desire for cleanliness, removal of traditional stoves, and perceptions of luck. Barriers to LPG use included: fears of LPG, problems with LPG brands, delays in obtaining LPG refills, social pressure, perceived incompatibility of traditional dishes, perceived inability to use clay pots, separate kitchens for LPG and traditional stoves, designated pots for use on the traditional stove, and lack of heat. However, these barriers did not prevent participants from using LPG nearly exclusively. Results suggest that social and cultural barriers to exclusive LPG use can be overcome when LPG stoves and fuel are provided at no cost to users and supplemented with behavioral support. Governments should evaluate the economic feasibility and sustainability of LPG subsidization, considering the potential benefits of exclusive LPG use.